Intervention policy of the BoJ: A unified approach - Beine, Michel; Bernal, Oscar; Gnabo, Jean-Yves; Lecourt, Christelle (Journal of Banking & Finance, 2009)
Intervening in the FX market implies a complex decision process for central banks. Monetary authorities have to decide whether to intervene or not, and if so, when and how. Since the successive steps of this procedure are likely to be highly interdependent, we adopt a nested logit approach to capture their relationships and to characterize the prominent features of the various steps of the intervention decision process. Our estimations based on Japanese data from 1991 to 2004 indicate that the Bank of Japan: (i) mainly reacted to deviations of the exchange rate with respect to fundamentals and (ii) tended to favour secrecy when its credibility was low. We also provide new insights on the so-called secrecy puzzle by modeling explicitly the risk for a secret intervention to be detected. Our results have important implications in terms of exchange rate policy, such as the emergence of a trade-off between intervention size, communication policy and secrecy. Our results tend to provide some explanation for the observed persistence of ineffective intervention policy during some sub-periods.